Biosurfactants from marine thermophilic bacilli for mitigating soil dehydration and preventing plant diseases - V. Zammuto; A. Macrì; M. T. Caccamo; S. Magazù; E. Conti; D. Leone; A. Spanò; C. Gugliandolo (International Journal of Environmental Science and Technology, 2026)

Biopsychosocial frailty and the incident risk of cardio- and cerebrovascular diseases: an 8-year follow-up of the italian longitudinal study on aging - Vincenzo Solfrizzi; Emanuele Scafato; Madia Lozupone; Carlo Custodero; Vittorio Dibello; Donato Cirrottola; Claudio Pace; Marika Rizzato; Andrea Schilardi; Claudia Gandin; Silvia Ghirini; Rodolfo Sardone; et al. (GeroScience, 2026)

Corrigendum to “Edaphobase 2.0: Advanced international data warehouse for collating and using soil biodiversity datasets” [Applied Soil Ecology 204 (2024) 105710] - D.J. Russell; E. Naudts; N.A. Soudzilovskaia; M.J.I. Briones; M. Çakır; E. Conti; J. Cortet; C. Fiera; D. Hackenberger Kutuzovic; M. Hedde; K. Hohberg; D. Indjic; et al. (Applied Soil Ecology, 2026)

Exploring light-effects of microalgal extract on zebrafish caudal fin cell regeneration for aquaculture applications - F. Conti; E. Frigato; E. Ruohisto; J. F. López-Olmeda; F. J. Sánchez-Vázquez; C. Baldisserotto; C. Bertolucci; S. Pancaldi (Aquaculture International, 2026)

The daily rhythms of temperature preference are conserved in nocturnal and blind fish - F. Conti; E. Gatto; G. de Alba; S. Pintos; J.F. López-Olmeda; L.M. Vera; S. Rey Planellas; S.A. Mackenzie; C. Bertolucci; F.J. Sánchez-Vázquez (Journal of Thermal Biology, 2025)

Are environmental factors correlated with the diversity of Phytophthora in organically and conventionally managed citrus orchards in Sicily? Insights from metabarcoding and baiting - Sebastiano Conti Taguali; Federico La Spada; Antonella Pane; Peter J. A. Cock; Beatrix Keillor; David E. L. Cooke; Santa Olga Cacciola (Mycological Progress, 2025)
Phytophthora species pose a significant threat to citrus production in the Mediterranean, particularly in Sicily, a major citrus-producing region. This study explores the diversity and distribution of Phytophthora taxa in Sicilian citrus orchards, addressing the urgent need to tackle increasing agricultural challenges, such as climate change. Specifically, it aimed to evaluate how environmental factors, such as the type of management (organic vs. conventional) and geographical area influence the composition of Phytophthora communities in Sicilian citrus orchards, and whether these communities correlate with tree health. An additional objective was to compare the effectiveness of traditional baiting and high-throughput metabarcoding techniques (targeting the ITS1 region and RPS10 gene) in capturing this diversity, as well as to assess potential shifts in community structure resulting from climate change by comparing current data with historical records. Soil samples were collected from ten citrus-producing areas under two distinct agronomic management and tree health conditions. Traditional baiting recovered 556 isolates of three already described Phytophthora species, while ITS1 metabarcoding identified ten additional taxa, demonstrating higher specificity (99.5% of ITS1 reads classified as Phytophthora compared to 82.5% for RPS10 ). Our findings indicate that geographical location is a key driver of community composition. Although statistical analyses did not reveal significant differences in Phytophthora diversity between organic and conventional management systems, these results provide valuable insights into the factors shaping pathogen communities. These insights are crucial for developing targeted disease management strategies and for understanding how environmental stressors, including climate change, impact pathogen dynamics in Mediterranean citrus orchards. Graphical Abstract

Extracellular vesicle-associated miR-222-3P and miR-186-5P as hypoxic markers in canine osteosarcoma: An in vitro study - R. De Maria; L. Maniscalco; M. Poncina; S. Divari; L. Parisi; S. Sonia; L. Cesar Conti; E. Mazzone; L. Aresu (Journal of Comparative Pathology, 2025)

Immunohistochemical profiling of B7-H3 expression in canine solid and liquid neoplasms - L. Cesar Conti; S. Capellero; S. Divari; L. Maniscalco; E. Mazzone; M. Olimpo; L. Aresu; R. De Maria (Journal of Comparative Pathology, 2025)

Charting the uncharted: Broad-scale benthic habitat distribution in the Brazilian continental margin - Vitor de Souza; Ibon Galparsoro; Tiago B. Gandra; Luis A. Conti; Marinez E. Scherer; Jarbas Bonetti (Estuarine, Coastal and Shelf Science, 2025)

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

The potential mediating role of the gut microbiome and metabolites in the association between PFAS and kidney function in young adults: A proof-of-concept study - Hailey E. Hampson; Shiwen Li; Douglas I. Walker; Hongxu Wang; Qiran Jia; Sarah Rock; Elizabeth Costello; Petter Bjornstad; Laura Pyle; Jonathan Nelson; Frank D. Gilliland; Zhanghua Chen; et al. (Science of The Total Environment, 2024)

Edaphobase 2.0: Advanced international data warehouse for collating and using soil biodiversity datasets - D.J. Russell; E. Naudts; N.A. Soudzilovskaia; M.J.I. Briones; M. Çakır; E. Conti; J. Cortet; C. Fiera; D. Hackenberger Kutuzovic; M. Hedde; K. Hohberg; D. Indjic; et al. (Applied Soil Ecology, 2024)

Observations on the role of internal sand moisture dynamics in wave-driven dune face erosion - S. Conti; K.D. Splinter; E. Booth; D. Djadjiguna; I.L. Turner (Geomorphology, 2024)

Weak phylogenetic effect on specialist plant assemblages and their persistence on habitat islands - Adam Klimeš; Rafael Molina‐Venegas; Angelino Carta; Milan Chytrý; Luisa Conti; Lars Götzenberger; Michal Hájek; Michal Horsák; Borja Jiménez‐Alfaro; Jitka Klimešová; Francisco E. Méndez‐Castro; David Zelený; et al. (Journal of Biogeography, 2024)
Aim The influence of species phylogenetic relatedness on the formation of insular assemblages remains understudied in functional island biogeography, especially for terrestrial habitat islands (i.e. distinct habitat patches embedded in a matrix that differ in the prevailing environmental conditions). Here, we tested three eco‐evolutionary hypotheses: (1) functional specialization of species (i.e. specialism) is associated with phylogenetic clustering at the habitat archipelago scale, (2) such clustering increases with insularity at the habitat island scale and (3) traits indicative of effective local persistence strategies shape island specialism. Location Terrestrial habitat islands, Europe (Fens in the Western Carpathians, Outcrops in Moravia and Mountaintops in the Cantabrian Range). Taxon Angiosperms. Methods We assessed the phylogenetic relatedness of habitat specialists in three different archipelagos composed of terrestrial habitat islands based on phylogenetic signals and phylogenetic diversity (PD) measures. We estimated the effect of insularity on PD using linear models and the effect of persistence traits on specialism using phylogenetic logistic regressions. Results Our hypotheses were largely not supported. Outcrop and mountaintop specialist assemblages did not exhibit any phylogenetic structuring, whereas fen specialists were clustered at the archipelago scale. Therefore, insularity seems not to act as a selective force for phylogenetic structure, and ecologically important persistence traits do not operate as precursors of specialism. Main Conclusions Our results show that species phylogenetic relatedness plays a minor role in shaping habitat island specialist assemblages. Furthermore, the effects of phylogenetic relatedness on assemblages of island specialists are system and scale dependent. Finally, accounting for species' phylogenetic relatedness on persistence traits yielded results similar to previous studies, which corroborates the positive relationship between insularity and functional traits (indicative of enhanced plant persistence abilities with increasing within‐archipelago insularity).

Expression of miRNA from spent pre-implantation embryos culture media - Claudia Omes; Alice Conti; Laura Benedetti; Veronica Tomasoni; Davide De Marchi; Rossella E. Nappi; M. Gabriella Cusella De Angelis; Gabriele Ceccarelli (Reproductive Biology, 2024)

Severe prenatal shocks and adolescent health: Evidence from the Dutch Hunger Winter - Gabriella Conti; Stavros Poupakis; Peter Ekamper; Govert E. Bijwaard; L.H. Lumey (Economics & Human Biology, 2024)

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

Screening, classification, capacity estimation and reservoir modelling of potential CO2 geological storage sites in the NW Adriatic Sea, Italy - Giampaolo Proietti; Alessia Conti; Stan E. Beaubien; Sabina Bigi (International Journal of Greenhouse Gas Control, 2023)

Evidence for trophic niche partitioning among three temperate gorgonian octocorals - Inga E. Conti-Jerpe; Joseph R. Pawlik; Christopher M. Finelli (Coral Reefs, 2022)
Trophic niche theory predicts that species in competition for a limiting resource will evolve adaptations allowing them to consume alternative resources and occupy new niche space. Trophic niche partitioning is often identified by differences in the morphology of feeding structures across species; however, these differences may not always be readily observable. Due to their constrained polyp morphology, octocorals are often viewed a single functional group that contributes to benthic-pelagic coupling by feeding opportunistically on available particles. To test the hypothesis that sympatric gorgonians share the same trophic niche, feeding selectivity of three gorgonian species ( Leptogorgia virgulata, Muricea pendula, and Thesea nivea) was compared using a combination of flume experiments and stable isotope analysis. The tentacle length and polyp surface area of L. virgulata and T. nivea were also measured and compared. In flume experiments, clearance of rotifers (“typical” zooplankton) and a mixture of cultured phytoplankton indicated that L. virgulata and T. nivea fed on zooplankton and not phytoplankton. Stable isotope values for all three species are consistent with distinct trophic niches, with M. pendula occupying a lower trophic level. Thesea nivea was found to have significantly larger polyp surface area and tentacle length; however, this did not appear to explain observed trophic differences. The results of this study provide evidence for niche partitioning, but future work is required to better understand the mechanism behind this divergence.

Insularity promotes plant persistence strategies in edaphic island systems - Luisa Conti; Francisco E. Méndez‐Castro; Milan Chytrý; Lars Götzenberger; Michal Hájek; Michal Horsák; Borja Jiménez‐Alfaro; Jitka Klimešová; David Zelený; Gianluigi Ottaviani (Global Ecology and Biogeography, 2022)
Aim Trait‐based approaches are being used increasingly in island biogeography, providing key insights into the eco‐evolutionary dynamics of insular systems. However, the determinants of persistence of plant species after they have arrived and established on an island remain largely unexplored. Here, we used three edaphic island systems (i.e., habitat patches distinguished from the landscape matrix by distinct soil conditions and specialized vegetation) to examine relationships between persistence strategies (those associated with clonality, bud bank, seed mass and life‐form) and insularity. We hypothesized that insularity promotes and selects strategies to persist locally, such that species occurring on small and/or isolated edaphic islands show trait values indicative of enhanced persistence and lower functional diversity. Location Three European systems of edaphic islands in the Western Carpathians, Moravia and the Cantabrian Range. Time period Present. Major taxa studied Vascular plants. Methods For each system, we used linear models to explore persistence‐related plant trait patterns (mean trait values and functional diversity) in relationship to three insularity metrics (island size, isolation and target effect). We focused on patterns of edaphic island specialists because their presence is confined to the islands. Results We found that insularity metrics largely explained the variation of the mean value and diversity of persistence‐related traits of edaphic island plant specialists. Specifically, insularity was positively related to traits supporting local persistence (e.g., more extensive lateral spread) and to a reduced variability in persistence traits. More insular systems showed stronger and more numerous trait–insularity links. Main conclusions Insularity can affect plant species diversity, form and function in edaphic island systems, such as selecting for enhanced and less diverse persistence strategies. Plant species occurring in insular systems might therefore avoid or delay local extinction by promoting adaptive strategies to persist in situ .

Effects of tetracycline on entomopathogenic nematodes and their bacterial symbionts - M. Clausi; D. Leone; A. Strano; A. Lizio; G. Rappazzo; C. Mulder; E. Conti (Ecotoxicology, 2021)

Genetic basis of susceptibility to low‐dose paraquat and variation between the sexes in Drosophila melanogaster - Pamela C. Lovejoy; Kate E. Foley; Melissa M. Conti; Samantha M. Meadows; Christopher Bishop; Anthony C. Fiumera (Molecular Ecology, 2021)
Toxicant resistance is a complex trait, affected both by genetics and the environment. Like most complex traits, it can exhibit sexual dimorphism, yet sex is often overlooked as a factor in studies of toxicant resistance. Paraquat, one such toxicant, is a commonly used herbicide and is known to produce mitochondrial oxidative stress, decrease dopaminergic neurons and dopamine (DA) levels, and decrease motor ability. While the main effects of paraquat are well‐characterized, less is known about the naturally occurring variation in paraquat susceptibility. The purpose of this study was to map the genes contributing to low‐dose paraquat susceptibility in Drosophila melanogaster , and to determine if susceptibility differs between the sexes. One hundred of the Drosophila Genetic Reference Panel (DGRP) lines were scored for susceptibility via climbing ability and used in a genome‐wide association study (GWAS). Variation in seventeen genes in females and thirty‐five genes in males associated with paraquat susceptibility. Only two candidate genes overlapped between the sexes despite a significant positive correlation between male and female susceptibilities. Many associated polymorphisms had significant interactions with sex, with most having conditionally neutral effects. Conditional neutrality between the sexes probably stems from sex‐biased expression which may result from partial resolution of sexual conflict. Candidate genes were verified with RNAi knockdowns, gene expression analyses, and DA quantification. Several of these genes are novel associations with paraquat susceptibility. This research highlights the importance of assessing both sexes when studying toxicant susceptibility.

Barcoding helps threatened species: the case of Iris marsica (Iridaceae) from the protected areas of the Abruzzo (Central Italy) - O. De Castro; E. Del Guacchio; E. Di Iorio; A. Di Maio; L. Di Martino; F. Bartolucci; F. Conti (Plant Biosystems, 2020)

Molecular fossils as a tool for tracking Holocene sea‐level change in the Loch of Stenness, Orkney - Martina L. G. Conti; Martin R. Bates; Richard C. Preece; Kirsty E. H. Penkman; Brendan J. Keely (Journal of Quaternary Science, 2020)
Sediments deposited in the Loch of Stenness (Orkney Islands, Scotland) during the Holocene transgression, previously dated to between ~5939–5612 bp , were analysed for molecular fossils – lipids and chlorophyll pigments from primary producers – that complement conventional microfossil and lithological approaches for studying past sea‐level change. While microfossil and lithological studies identified a transgression between 102 and 81 cm core depth, key molecular fossils fluctuate in occurrence and concentration between 118 and 85 cm, suggesting an earlier start to the transgression. Terrestrial lipid concentrations decreased and algal‐derived, short‐chain, n ‐alkanoic acid concentrations increased at 118 cm, indicating a disruption of the freshwater lake conditions associated with the early stages of the marine transgression. The lipid and pigment analyses provided information that complements and extends that from microfossil analysis, presenting a more complete record of Holocene sea‐level changes and local vegetation changes in the Loch of Stenness. The isostatic stability of Stenness during the Holocene points towards other factors to explain the transgression, such as regional factors and/or melting of the Antarctic ice sheet (which occurred up to 3 ka).

Correction to: Infectious mononucleosis, immune genotypes, and non-Hodgkin lymphoma (NHL): an InterLymph Consortium study - Niquelle Brown Wadé; Cindy M. Chang; David Conti; Joshua Millstein; Christine Skibola; Alexandra Nieters; Sophia S. Wang; Silvia De Sanjose; Eleanor Kane; John J. Spinelli; Paige Bracci; Yawei Zhang; et al. (Cancer Causes & Control, 2020)

Preservation of 34S-enriched sulfides in fossil sulfate-methane transition zones: new evidence from Miocene outcrops of the northern Apennines (Italy) - C. Argentino; J. E. Johnson; S. Conti; C. Fioroni; D. Fontana (Geo-Marine Letters, 2020)

Infectious mononucleosis, immune genotypes, and non-Hodgkin lymphoma (NHL): an InterLymph Consortium study - Niquelle Brown Wadé; Cindy M. Chang; David Conti; Joshua Millstein; Christine Skibola; Alexandra Nieters; Sophia S. Wang; Silvia De Sanjose; Eleanor Kane; John J. Spinelli; Paige Bracci; Yawei Zhang; et al. (Cancer Causes & Control, 2020)

Age-related murine hippocampal CA1 laminae oxidative stress measured in vivo by QUEnch-assiSTed (QUEST) MRI: impact of isoflurane anesthesia - Bruce A. Berkowitz; Robert H. Podolsky; Karen Lins Childers; Alexander Gow; Brandy L. Schneider; Scott C. Lloyd; Kelly E. Bosse; Alana C. Conti; Robin Roberts; Ali M. Berri; Emma Graffice; Kenan Sinan; et al. (GeroScience, 2020)
Age-related impairments in spatial learning and memory often precede non-familial neurodegenerative disease. Ex vivo studies suggest that physiologic age-related oxidative stress in hippocampus area CA1 may contribute to prodromal spatial disorientation and to morbidity. Yet, conventional blood or cerebrospinal fluid assays appear insufficient for early detection or management of oxidative stress within CA1 sub-regions in vivo. Here, we address this biomarker problem using a non-invasive MRI index of CA1 laminae oxidative stress based on reduction in R1 (= 1/T1) after anti-oxidant administration. An R1 reduction reflects quenching of continuous and excessive production of endogenous paramagnetic free radicals. Careful motion-correction image acquisition, and avoiding repeated exposure to isoflurane, facilitates detection of hippocampus CA1 laminae oxidative stress with QUEnch-assiSTed (QUEST) MRI. Intriguingly, age- and isoflurane-related oxidative stress is localized to the stratum lacunosum of the CA1 region. Our data raise the possibility of using QUEST MRI and FDA-approved anti-oxidants to remediate spatial disorientation and later neurodegeneration with age in animals and humans.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Plant–environment interactions through a functional traits perspective: a review of Italian studies - Stefano Chelli; Michela Marignani; Elena Barni; Alessandro Petraglia; Giacomo Puglielli; Camilla Wellstein; Alicia T. R. Acosta; Rossano Bolpagni; Luca Bragazza; Giandiego Campetella; Alessandro Chiarucci; Luisa Conti; et al. (Plant Biosystems, 2019)

Comparative serum bactericidal activity of meropenem-based combination regimens against extended-spectrum beta-lactamase and KPC-producing Klebsiella pneumoniae - Paolo Gaibani; Donatella Lombardo; Michele Bartoletti; Simone Ambretti; Caterina Campoli; Maddalena Giannella; Sara Tedeschi; Matteo Conti; Rita Mancini; Maria Paola Landini; Maria Carla Re; Pierluigi Viale; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Developing allometric models to predict the individual aboveground biomass of shrubs worldwide - G. Conti; L. D. Gorné; S. R. Zeballos; M. L. Lipoma; G. Gatica; E. Kowaljow; J. I. Whitworth‐Hulse; A. Cuchietti; M. Poca; S. Pestoni; P. M. Fernandes (Global Ecology and Biogeography, 2019)
Aim Existing global models to predict standing biomass are based on trees characterized by a single principal stem, well developed in height. However, their use in open woodlands and shrublands, characterized by multistemmed species with substantial crown development, generates a high level of uncertainty in biomass estimates. This limitation led us to (a) develop global models of shrub individual aboveground biomass based on simple allometric variables, (b) to compare the fit of these models with existing global biomass models, and (c) to assess whether models fit change when bioclimatic variables are considered. Location Global. Time period Present. Major taxa studied 118 species of shrubs. Methods We compile a database of 3,243 individuals across 49 sites distributed worldwide. Including stem basal diameter, height and crown diameter as predictor variables, we built potential models and compared their fit using generalized least squares. We used mixed effects models to determine if bioclimatic variables improved the accuracy of biomass models. Results Although the most important variable in terms of predictive capacity was stem basal diameter, crown diameter significantly improved the models’ fit, followed by height. Four models were finally chosen, with the best model combining all these variables in the same equation [ R 2 = 0.930, root mean square error (RMSE) = 0.476]. Selected models performed as well as established global biomass models. Including the individual bioform significantly improved the models’ fit. Main conclusions Stem basal diameter, crown diameter and height measures could be combined to provide robust aboveground biomass (AGB) estimates of individual shrub species. Our study supplements well‐established models developed for trees, allowing more accurate biomass estimation of multistemmed woody individuals. We further provide tools for a methodological standardization of individual biomass quantification in these species. We expect these results contribute to improve the quality of biomass estimates across ecosystems, but also to generate methodological consensus on field biomass assessments in shrubs.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Calcium/calmodulin-stimulated adenylyl cyclases 1 and 8 regulate reward-related brain activity and ethanol consumption - Kelly E. Bosse; Farhad Ghoddoussi; Ajay T. Eapen; Jennifer L. Charlton; Laura L. Susick; Kirt Desai; Bruce A. Berkowitz; Shane A. Perrine; Alana C. Conti (Brain Imaging and Behavior, 2019)

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

An updated checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Albano; A. Alessandrini; N. M. G. Ardenghi; G. Astuti; G. Bacchetta; S. Ballelli; E. Banfi; G. Barberis; L. Bernardo; et al. (Plant Biosystems, 2018)

The starch-bound alpha-amylase/trypsin-inhibitors in Avena - Laura Gazza; Gloria Gazzelloni; Federica Taddei; Arianna Latini; Vera Muccilli; Michela Alfieri; Salvatore Conti; Rita Redaelli; Norberto E. Pogna (Molecular Genetics and Genomics, 2016)

Altered soil carbon dynamics under different land-use regimes in subtropical seasonally-dry forests of central Argentina - G. Conti; E. Kowaljow; F. Baptist; C. Rumpel; A. Cuchietti; N. Pérez Harguindeguy; S. Díaz (Plant and Soil, 2016)

Allopatric speciation with little niche divergence is common among alpine Primulaceae - Florian C. Boucher; Niklaus E. Zimmermann; Elena Conti (Journal of Biogeography, 2016)
Aim Despite the accumulation of cases describing fast radiations of alpine plants, we still have limited understanding of the drivers of speciation in alpine floras and of the precise the timing of their diversification. Here, we investigated spatial and temporal patterns of speciation in three groups of alpine Primulaceae. Location Mountains of the European Alpine System. Methods We built a new phylogeny of Primulaceae including all species in three focal groups: Androsace sect. Aretia , Primula sect. Auricula and Soldanella . Combining phylogenetic information with a detailed climatic data set, we investigated patterns of range and ecological overlap between sister‐species using an approach that takes phylogenetic uncertainty into account. Finally, we investigated temporal trajectories of diversification in the three focal groups. Results We found that a large majority of sister‐species pairs in the three groups are strictly allopatric and show little differences in substrate and climatic preferences, a result that was robust to phylogenetic uncertainty. While rates of diversification have remained constant in Soldanella , both Androsace sect. Aretia and Primula sect. Auricula showed decreased diversification rates in the Pleistocene compared to previous geological epochs. Main conclusions Allopatric speciation with little niche divergence appears to have been by far the most common mode of speciation across the three groups studied. A few examples, however, suggest that ecological and polyploid speciation might also have played a role in the diversification of these three groups. Finally, extensive diversification likely occurred in the late Miocene and Pliocene coinciding with the later phases of the Alpine uplift, while diversification slowed down during subsequent glacial cycles of the Pleistocene.

Biochemical and molecular characterization of Avena indolines and their role in kernel texture - Laura Gazza; Federica Taddei; Salvatore Conti; Gloria Gazzelloni; Vera Muccilli; Michela Janni; Renato D’Ovidio; Michela Alfieri; Rita Redaelli; Norberto E. Pogna (Molecular Genetics and Genomics, 2015)

Islands as model systems in ecology and evolution: prospects fifty years after MacArthur‐Wilson - Ben H. Warren; Daniel Simberloff; Robert E. Ricklefs; Robin Aguilée; Fabien L. Condamine; Dominique Gravel; Hélène Morlon; Nicolas Mouquet; James Rosindell; Juliane Casquet; Elena Conti; Josselin Cornuault; et al. (Ecology Letters, 2015)
The study of islands as model systems has played an important role in the development of evolutionary and ecological theory. The 50th anniversary of MacArthur and Wilson's (December 1963) article, ‘An equilibrium theory of insular zoogeography’, was a recent milestone for this theme. Since 1963, island systems have provided new insights into the formation of ecological communities. Here, building on such developments, we highlight prospects for research on islands to improve our understanding of the ecology and evolution of communities in general. Throughout, we emphasise how attributes of islands combine to provide unusual research opportunities, the implications of which stretch far beyond islands. Molecular tools and increasing data acquisition now permit re‐assessment of some fundamental issues that interested MacArthur and Wilson. These include the formation of ecological networks, species abundance distributions, and the contribution of evolution to community assembly. We also extend our prospects to other fields of ecology and evolution – understanding ecosystem functioning, speciation and diversification – frequently employing assets of oceanic islands in inferring the geographic area within which evolution has occurred, and potential barriers to gene flow. Although island‐based theory is continually being enriched, incorporating non‐equilibrium dynamics is identified as a major challenge for the future.

Comparative safety profiles of intravitreal bevacizumab, ranibizumab and pegaptanib: the analysis of the WHO database of adverse drug reactions - C. Biagi; V. Conti; N. Montanaro; M. Melis; E. Buccellato; M. Donati; A. Covezzoli; R. Amato; L. Pazzi; M. Venegoni; A. Vaccheri; D. Motola (European Journal of Clinical Pharmacology, 2014)

Topo‐climatic microrefugia explain the persistence of a rare endemic plant in the Alps during the last 21 millennia - Theofania S. Patsiou; Elena Conti; Niklaus E. Zimmermann; Spyros Theodoridis; Christophe F. Randin (Global Change Biology, 2014)
Ongoing rapid climate change is predicted to cause local extinction of plant species in mountain regions. However, some plant species could have persisted during Quaternary climate oscillations without shifting their range, despite the limited evidence from fossils. Here, we tested two candidate mechanisms of persistence by comparing the macrorefugia and microrefugia ( MR ) hypotheses. We used the rare and endemic Saxifraga florulenta as a model taxon and combined ensembles of species distribution models ( SDM s) with a high‐resolution paleoclimatic and topographic dataset to reconstruct its potential current and past distribution since the last glacial maximum. To test the macrorefugia hypothesis, we verified whether the species could have persisted in or shifted to geographic areas defined by its realized niche. We then identified potential MR based on climatic and topographic properties of the landscape and applied refined scenarios of MR dynamics and functions over time. Last, we quantified the number of known occurrences that could be explained by either the macrorefugia or MR model. A consensus of two or three SDM techniques predicted absence between 14–10, 3–4 and 1 ka bp , which did not support the macrorefugia model. In contrast, we showed that S. florulenta could have contracted into MR during periods of absence predicted by the SDM s and later re‐colonized suitable areas according to the macrorefugia model. Assuming a limited and realistic seed dispersal distance for our species, we explained a large number of the current occurrences (61–96%). Additionally, we showed that MR could have facilitated range expansions or shifts of S. florulenta . Finally, we found that the most recent and the most stable MR were the ones closest to current occurrences. Hence, we propose a novel paradigm to explain plant persistence by highlighting the importance of supporting functions of MR when forecasting the fate of plant species under climate change.

Are Red Lists really useful for plant conservation? The New Red List of the Italian Flora in the perspective of national conservation policies - G. Rossi; C. Montagnani; T. Abeli; D. Gargano; L. Peruzzi; G. Fenu; S. Magrini; M. Gennai; B. Foggi; R.P. Wagensommer; S. Ravera; A. Cogoni; et al. (Plant Biosystems, 2014)

Distribution range and ecological niche of Primula marginata Curtis (Primulaceae) - G. Casazza; S. Marsili; L. Granato; E. Conti; V. Noble; A. Selvaggi; L. Minuto (Plant Biosystems, 2013)

Lead Bone Toxicity in Growing Rats Exposed to Chronic Intermittent Hypoxia - María I. Conti; Clarisa Bozzini; Graciela B. Facorro; Ching M. Lee; Patricia M. Mandalunis; Lidia L. Piehl; Adriana E. Piñeiro; Antonela R. Terrizzi; María P. Martínez (Bulletin of Environmental Contamination and Toxicology, 2012)

Effects of Lead Exposure on Growth and Bone Biology in Growing Rats Exposed to Simulated High Altitude - María Inés Conti; Antonela R. Terrizzi; Ching Ming Lee; Patricia M. Mandalunis; Clarisa Bozzini; Adriana E. Piñeiro; María del Pilar Martínez (Bulletin of Environmental Contamination and Toxicology, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Fine resolution distribution modelling of endemics in Majella National Park, Central Italy - H. van Gils; F. Conti; G. Ciaschetti; E. Westinga (Plant Biosystems, 2012)

A case of primary papillary disseminated adenocarcinoma of canine lung - Maria Beatrice Conti; M. C. Marchesi; G. Angeli; E. Lepri; C. Marinetti; F. Rueca (Veterinary Research Communications, 2010)

Non‐native flora of Italy: Species distribution and threats - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; S. Assini; E. Banfi; E. Barni; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; et al. (Plant Biosystems, 2010)

Inventory of the non‐native flora of Italy - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; E. Banfi; L. Bernardo; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; S. Fascetti; et al. (Plant Biosystems, 2009)

Clinical findings and diagnosis in a case of cholangiocellular carcinoma in a horse - M. B. Conti; M. C. Marchesi; F. Zappulla; D. Buttarelli; E. Lepri; F. Passamonti; S. Galletti; G. Rucco; F. Rueca (Veterinary Research Communications, 2008)

Soil N2O emissions and N2O/(N2O+N2) ratio as affected by different fertilization practices and soil moisture - E. Ciarlo; M. Conti; N. Bartoloni; G. Rubio (Biology and Fertility of Soils, 2008)

Nitrous oxide emissions from soil during soybean [(Glycine max (L.) Merrill] crop phenological stages and stubbles decomposition period - Ignacio A. Ciampitti; Esteban A. Ciarlo; Marta E. Conti (Biology and Fertility of Soils, 2008)

Platelet Lysate Promotes in Vitro Proliferation of Equine Mesenchymal Stem Cells and Tenocytes - M. Del Bue; S. Riccò; V. Conti; E. Merli; R. Ramoni; S. Grolli (Veterinary Research Communications, 2007)

The effect of moisture on nitrous oxide emissions from soil and the N2O/(N2O+N2) ratio under laboratory conditions - E. Ciarlo; M. Conti; N. Bartoloni; G. Rubio (Biology and Fertility of Soils, 2007)

Fungal abundance and distribution as influenced by clearing and land use in a vertic soil of Argentina - E. Gomez; R. Pioli; M. Conti (Biology and Fertility of Soils, 2006)

Multivariate evaluation by quality indicators of no-tillage system in Argiudolls of rolling pampa (Argentina) - Lidia Giuffré; Romina Romaniuk; Marta E. Conti; Norberto Bartoloni (Biology and Fertility of Soils, 2006)

Diet and cooling interactions on physiological responses of grazing dairy cows, milk production and composition - M. R. Gallardo; S. E. Valtorta; P. E. Leva; M. C. Gaggiotti; G. A. Conti; R. F. Gregoret (International Journal of Biometeorology, 2005)

A phylogenetic analysis of Apostasioideae (Orchidaceae) based on ITS, trnL-F and matK sequences - A. Kocyan; Y.-L. Qiu; P. K. Endress; E. Conti (Plant Systematics and Evolution, 2004)

Dynamics of humic fractions and microbial activity under no-tillage or reduced tillage, as compared with native pasture (Pampa Argentina) - Mirta G. Gonzlez; Marta E. Conti; R. Martha Palma; Nilda M. Arrigo (Biology and Fertility of Soils, 2003)

Chemical and biochemical properties as potential indicators of disturbances - N. M. Arrigo; M. E. Conti; R. M. Palma; M. I. Saubidet (Biology and Fertility of Soils, 2000)

Geochemical changes at the Bagni di Triponzo thermal spring during the Umbria-Marche 1997–1998 seismic sequence - F. Quattrocchi; R. Pik; L. Pizzino; M. Guerra; P. Scarlato; M. Angelone; M. Barbieri; A. Conti; B. Marty; E. Sacchi; G.M. Zuppi; S. Lombardi (Journal of Seismology, 2000)

IgG, IgG1 and IgM response in Trichinella spiralis-infected mice treated with 4-deoxypirydoxine or fed a Vitamin B6-deficient diet - S. Frydas; M. Reale; D. Vacalis; R.C. Barbacane; F.C. Placido; I. Cataldo; M. Di Gioacchino; E. Karagouni; E. Dotsika; G. Anogiannakis; A. Trakatellis; P. Conti (Molecular and Cellular Biochemistry, 1999)

Expression of lymphocyte subpopulations, cytokine serum levels, and blood and urinary trace elements in asymptomatic atopic men exposed to an urban environment - P. Boscolo; M. Di Gioacchino; E. Sabbioni; F. Benvenuti; P. Conti; M. Reale; P. Bavazzano; G. Giuliano (International Archives of Occupational and Environmental Health, 1999)

RFLP mapping of quantitative trait loci controlling abscisic acid concentration in leaves of drought-stressed maize (Zea mays L.) - R. Tuberosa; M. C. Sanguineti; P. Landi; S. Salvi; E. Casarini; S. Conti (Theoretical and Applied Genetics, 1998)

Influence of tillage system on denitrification in maize-cropped soils - R. M. Palma; M. Rímolo; M. I. Saubidet; M. E. Conti (Biology and Fertility of Soils, 1997)

Relationship of soil carbon light fraction, microbial activity, humic acid production and nitrogen fertilization in the decaying process of corn stubble - M. E. Conti; N. M. Arrigo; H. J. Marelli (Biology and Fertility of Soils, 1997)